Bill of Lading
1938-02-01 030-0210-005 Terms and Exceptions referred to in Clause 1 (C) of this Bill of Lading. A. Handling, Custody and Care of the Goods when not within the Ship's Rail. The Carrier shall not under any circumstance be liable for any loss of or damage or delay to any of the said goods from whatever cause arising before the goods cross the ship's rail for loading or after they cross the ship's rail on discharge from the ship, but such goods shall be at the sole risk of the shipper and/or owner of the goods during all such times (whether the goods are in the custody of the Carrier or not) even although such loss. damage or delay may be due to the wrongful act, neglect or default of the Carrier or of any stevedore, agent or servant engaged or employed by him, or of any person whomsoever for whom the Carrier may be responsible, whether in his service or not, or of any other carrier, and even though any ship or craft in which any of the said goods may be loaded was unseaworthy at the time of loading or sailing or at any other time. The above provisions shall apply whether the goods are in the custody of the Carrier or not and although the goods are being carried under a contract of through carriage by which land carriage, shipping, landing, lighterage, warehousing, or transhipping is to be done by or at the cost of the Carrier, and whether he is acting as Carrier or as wharfinger, lighterman, land carrier, or otherwise ; and in any of such cases the Carrier is authorised to employ or contract with other carriers of any kind (the terms, conditions and exceptions of such contract are incorporated herein, the owner of the goods being responsible for all additional expenses and/or liabilities resulting therefrom) whether by land or water or wharfingers for wharftng, carrying, or otherwise dealing with the said goods and neither the Carrier nor any of such persons shall be responsible for any loss, damage or delay to the said goods notwithstanding the negligence of themselves or their agents, servants, or any others whomsoever for whom they may be responsible and notwithstanding that any ship or craft in which the goods may be laden may be unseaworthy on shipment or sailing or at any other time. B. Stowage. The goods may be stowed in poop, forecastle, deck house, shelter deck or other covered-in space, commonly used in the trade for the carriage of goods. C. Voyage. All the liberties and other matters inserted under this Head and under heads E and F are agreed to be part of and within the scope of the contract voyage covered by this Bill of Lading. (1) The ship above-named and any other ship or ships or craft or conveyance into which the goods or any part thereof may be loaded under the provisions hereof shall have liberty— (a) To sail with or without Pilots, (b) To make trial trips or adjust compasses, (c) To tow vessels in all situations, (d) To carry livestock and to carry cargo on deck, (e) To carry goods of all kinds, dangerous or otherwise, (f) To proceed backwards and forwards, once or oftener, to or from and use any port or ports, in any rotation, for any purpose whatsoever, whether in, or out of, or behind or beyond the named ports or the customary or advertised route. (g) To dry dock for any purposes whatsoever with the whole or part of the cargo shipped under this Bill of Lading on board, at any time and place before or after sailing, or after arrival at the port of discharge. (2) The Carrier is at liberty to land and/or store the goods at any port or place and/or to tranship, forward or carry the goods to their port of destination, by the above or other ship or ships, or by any craft or conveyance, either belonging to himself or to others, so that the goods may proceed by any route, however circuitous, and whether directly or indirectly, to the port of destination, as and when the Carrier may in his discretion think fit, either by land or water, but at the Carrier's expense (except such expenses and liabilities as are provided for in clause A). (3) In case in the opinion of the Carrier or Master the ship shall be unable for any reason whatsoever to reach or enter the port or place of discharge, or in case of quarantine at the port or place of discharge, or of ice or weather rendering in the opinion of the Carrier or Master access to such port difficult or dangerous, or of the blockade or interdict or closingt or obstruction from any cause of any kind whatsoever of such port or place or the waters leading thereto, or in case at any time in the opinion of the Carrier or Master it is impracticable or inconvenient from any reason of any kind whatsoever (whether the ship shall or shall not have then arrived at the port or place of discharge) to discharge all the goods at the port or place of discharge, or in case of any actual or threatened strike, lock-out, riot or disturbance, or congestion on railways or in docks, at the port or place of discharge, which in the opinion of the Master is likely to prevent, hinder or delay the ship from reaching or immediately discharging and leaving the port or place of discharge or if in the opinion of the Carrier or Master entry into the port or place of discharge or Communication therewith would render the ship liable to quarantine at any subsequent port she might enter, then in any of such cases the Carrier or Master shall be entitled to discharge all or any of the goods at any other available port or place which he may consider suitable, or to take back the same to the port of shipment and there discharge the same, or retain the same on board until the ship shall reach the port of destination notwithstanding that the ship may meanwhile proceed on one or more additional voyages, or to transfer the same to another ship or craft, or to put the same on rail for their destination, and all such matters shall be at the risk of the shipper and/or owner of the goods. Any such discharge or dealing with the goods shall be deemed a final delivery thereof and a due performance of this bill of lading contract and the freight deemed to be duly earned. All expenses or losses incurred by any of the aforesaid matters of whatever kind shall be borne by the shipper and/or owner of the goods. Without prejudice to the foregoing provisions, the goods may in the event of quarantine at the port of discharge, at the option of the Carrier or Master, be discharged on arrival into quarantine depot, hulk, lighter or other craft at the risk and expense of the shipper and/or owner of the goods. It is hereby declared that it was the intention of both the Carrier and the Shipper that the goods should be actually put on board the above-named ship but if from any cause the goods or any part thereof were shut out, the Carrier shall have liberty to, and shall ship and carry the same upon the terms of this Bill of Lading on the next available ship of this Line, or (at the option of the Carrier) of any other Line, and such shipment and carriage shall then be the only shipment and carriage for which the Carrier is responsible. (4) The ship in addition to any liberties expressed or implied in this Bill ot Lading shall have liberty to comply with any orders or directions as to departure, arrival, routes, ports of call, stoppages or otherwise howsoever given by His Majesty's Government or any Department thereof or any person acting or purporting to act with the authority of that Government, or of any Department thereof, or by the Committee or person having under the terms of the War Risks Insurance on the ship, the right to give such orders or directions, and nothing done or not done by reason of any such orders or directions shall be deemed a deviation. (5) Consignees having an option as to ports of deliverv must declare 24 hours before the ship's arrival at her first port of discharge or the option will expire. D. Deviation. All the exceptions and stipulations in favour of the Carrier contained in this Bill of Lading shall continue to apply although the ship may have deviated from the contract voyage and although such deviation may amount to a change or abandonment of voyage, any warranty or rule of law to the contrary notwithstanding, and for the purpose of this contract all such deviations shall be deemed to be within the contract voyage. Without prejudice to the foregoing, should there be any deviation not permitted under this contract, it shall give rise only to a claim for loss or damage resulting therefrom and shall not avoid or displace the contract or any part thereof. E. Port, Customs, Consular and other Regulations. (1) If the Shipper has not furnished all particulars necessary to enable the Bill of Lading to be made out in accordance with the prescriptions and regulations of the Port, Customs, Consular or any other Authorities, and all Consular, Health or other Certificates required to accompany the goods, then all detention, charges or penalties accruing to the ship or her cargo owing to the want of any such particulars or certificates shall be borne and paid for by the Shipper and/or Owner of the goods. (2) The Consignee and/or Owner of the goods shall bear and pay all tonnage dues, shed dues, harbour dues, custom dues and charges, wharfage charges, and other dues and charges payable in respect of the goods. (3) The Shipper and/or Owner of the goods shall comply with the regulations and requirements of all Port, Customs and other Authorities, and shall bear and pay all duties, taxes, fines, imposts, expenses, loss or damage of whatever nature incurred or suffered by reason of the breach thereof, or of the illegal, incorrect or insufficient marking, numbering or addressing of packages, or description of their contents, and shall indemnify the Carrier and his agents and the ship and the Owners of the other cargo on board against all claims, demands, losses and expenses in respect thereof, and shall pay demurrage at the rate hereafter provided for any detention of the ship thereby caused. (4) In the event of the goods by reason of their not being marked with the name of the country from which they are exported, or for any other reasons of any kind, not complying with the Customs Regulations at the port of discharge, the Carrier shall be at liberty to bring back, or to re-ship such goods to the port of shipment at the sole risk and expense of the Shipper and/or Owner of the goods. (5) Should the Carrier desire to discharge, beyond usual Customs hours the Consignee and/or Owner of the goods shall, if so required, sign immediately an application for that purpose. F. Discharge. (1) The ship may commence discharching immediately on arrival without notice to the Consignee or Owner of the goods, and discharge continuously, irrespective of weather, by day and by night Sundays and holidays included, any custom of the port to the contrary notwithstanding, on to quay, or into hulk, depot or lighter or other craft of any kind as the Carrier or his agent may determine. The Carrier, his agents and servants shall not, under any circumstances whatever, be under any liability for failure to notify the Consignee or Owner of the goods of arrival of the goods, any custom of the port to the contrary notwithstanding. (2) The Consignee or Owner of the goods shall take delivery of the goods at the ship's rail as they come to hand and as fast as ship can deliver, and if he shall fail to do so the Carrier shall be at liberty to put the goods into craft of any kind and/or store and/or land the same on the quay either directly or after lightering the same, all at the expense and risk of the Consignee and/or Owner of the goods. Should the ship be delayed by reason of the default of the Consignee or Owner of the goods either under this Clause or otherwise howsoever he shall pay demurrage during such delay at the rate of 1/- per gross registered ton of the ship per day or pro rata. (3) Unclaimed goods, not otherwise accounted for shall at the Carrier's option be apportioned to the different Consignees of like goods according to shortages, and shall be accepted to the extent thereof. (4) If any Consignee has a shortage in the marks or numbers called for by this Bill of Lading, unclaimed goods of like kind and quality but of different marks or numbers, or of no marks or numbers, shall at the Carrier's option be deemed to constitute a part of the goods and be accepted by the Consignees as good delivery under this Bill of Lading. (5) (a) The Shipper and/or Owner of the goods shall supply the agent of the ship at the port of discharge with the necessary papers for passing the goods through the Custom House by the time of the Ship's arrival, and shall be liable for all loss damage or detention of any kind whatsoever incurred in default thereof. (b) In the event of there being no immediate opportunity for transhipping or forwarding the goods at or from the port of discharge of the above named ship to their ultimate destination, the Carrier shall be at liberty to enter and land the goods, or to put them into craft or store, at the sole risk and expense of the Consignee and/or Owner of the goods. (c) The Carrier or his agent may in respect of dutiable goods transhipped at the port of discharge give such undertaking as the Customs Authorities at the port require with respect to dealing with the goods at the port where duty is payable, and all charges involved or liabilities incurred shall be borne by the Consignee and/or Owner of the goods. (6) If the goods are made deliverable hereunder to a named Consignee, or to a named Consignee or assigns, and not to order or assigns, and the law in force at the port of discharge so requires, delivery may be made to such named Consignee without production or delivery of the Bill of Lading. G. General average shall be adjusted according to York-Antwerp Rules, 1924, save and except that no loss of, or injury to livestock, whether by jettison or otherwise, shall be recoverable. Such deposit as the Carrier or his Agent may deem sufficient to cover the estimated contribution of the goods and any special charges thereon shall, if required, be paid to the Carrier or his Agents previously to delivery and may be converted at any time and from time to time into any other currency if the Carrier shall think fit at the risk of the depositor. The adjustment shall be prepared in the United Kingdom. 292/946/30/210(v)